Alla Myzelev in Conversation with Marine Tanguy on Commercial Public Art and Art Agency - Myzelev, Alla (UXUC - User Experience and Urban Creativity, 2020)
An advocate for urban artists since a young age, Marine Tanguy launched MTArt Agency in 2015. MTArt is the first talent agency for visual artists worldwide. MTArt Agency was behind the largest public art painting in the world: the project of Saype in Paris supported by 30 companies including the Eiffel Tower and the Guardian Media Group.